Improved Interleaved Boost Converter with Soft-Switching: Analysis and Experimental Validation - Popuri, Madhuchandra; Bhajana, Veera Venkata Subrahmanya Kumar; Maharana, Manoj Kumar; Biswal, Pravat; Appasani, Bhargav; Oproescu, Mihai; Bizon, Nicu (Engineering, Technology & Applied Science Research, 2023)
This paper proposes a novel interleaved boost converter for renewable energy applications. The two-phase interleaved boost converter was improved with lossless passive snubber cells to ensure the Zero Voltage Switching (ZVS) condition. The ZVS condition is contributed by a resonant inductor, a resonant capacitor, and two diodes. The proposed converter was operated in continuous current mode on its primary side. The significant merits of this converter are reduced switching losses, better efficiency, and reduced input current ripples without auxiliary switches. The soft-switching ability of this converter is maintained under both light- and heavy-load conditions. This paper also presents the operating principles and design analysis of the proposed converter. Furthermore, a 50-320V prototype was operated at 250 W to validate the soft-switching operation and theoretical analysis, and the experimental results are presented.